A Qualitative Analysis of Ethical Perspectives on Recruitment and Consent for Human Intracranial Electrophysiology Studies. Issue 1 (2nd January 2021) - Mergenthaler, Joncarmen V.; Chiong, Winston; Dohan, Daniel; Feler, Josh; Lechner, Cailin R.; Starr, Philip A.; Arias, Jalayne J.
Abstract: Intracranial electrophysiological research methods, including those applying electrodes on the cortical surface or in deep structures, have become increasingly important in human neuroscience. They also pose novel ethical concerns, as human studies require the participation of neurological patients undergoing surgery for conditions such as epilepsy and Parkinson's disease. Research participants in this setting may be vulnerable to conflicts of interest, therapeutic misconception, and other threats to valid recruitment and consent. We conducted semi-structured interviews with investigators from NIH-funded studies involving recording or stimulation inside the human skull. We elicited perspectives on study recruitment and consent procedures, and analyzed transcripts using a modified grounded theory approach. We interviewed 26 investigators from 19 separate intracranial electrophysiology studies, who described two study types: opportunity studies ( n = 15) and experimental trials ( n = 4). Respondents described significant heterogeneity in recruitment and consent procedures, even among studies employing similar techniques. In some studies, clinician-investigators were specifically barred from obtaining consent, while in other studies clinician-investigators were specifically required to obtain consent; regulatory guidance was inconsistent. Respondents also described various models for subject selection, the timing of consent, and continuing consent for temporally extended studies. Respondents expressed ethical concerns about participants' vulnerability and the communication of research-related risks. We found a lack of consensus among investigators regarding recruitment and consent methods in human intracranial electrophysiology. This likely reflects the novelty and complexity of such studies and indicates a need for further discussion and development of best practices in this research domain.